2001
DOI: 10.1016/s0022-5347(05)65847-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality Preserving Cystectomy and Neobladder: Initial Results

Abstract: Sexuality preserving cystectomy and neobladder achieves maximal tissue conservation, resulting in preserved normal sexual function and satisfactory urinary tract reconstruction. Using strict criteria oncological results have not been jeopardized to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 12 publications
3
57
1
Order By: Relevance
“…In a series of 13 patients (10 males, 3 females), Horenblass reported that 7/10 men who underwent surgery with this modification had return of normal erections on Rigiscan measurement and all women (3/3) reported normal vaginal lubrication. 34 In a later update, this group reported that 20/24 males were sexually active with or without erectaids and concluded that Sexual dysfunction after pelvic surgery C Zippe et al preservation of the prostate and neurovascular pedicle led to improved sexual function. 35 The oncologic concern with this procedure is that prostatic urethra and seminal vesicles can be a potential site for recurrence.…”
Section: Ed In Malesmentioning
confidence: 99%
“…In a series of 13 patients (10 males, 3 females), Horenblass reported that 7/10 men who underwent surgery with this modification had return of normal erections on Rigiscan measurement and all women (3/3) reported normal vaginal lubrication. 34 In a later update, this group reported that 20/24 males were sexually active with or without erectaids and concluded that Sexual dysfunction after pelvic surgery C Zippe et al preservation of the prostate and neurovascular pedicle led to improved sexual function. 35 The oncologic concern with this procedure is that prostatic urethra and seminal vesicles can be a potential site for recurrence.…”
Section: Ed In Malesmentioning
confidence: 99%
“…To lower the risk of future malignancy following prostatesparing cystectomy, strict screening protocols are used to rule out adenocarcinoma and urothelial carcinoma of the prostate before surgery. 6 These measures do not preclude future development of malignancies, and definitive treatment can be more challenging following cystectomy given the loss of tissue planes and peri-prostatic inflammatory and fibrotic changes that occur with requisite urine leakage following the original prostate-sparing cystectomy neobladder surgery. Additionally, the anticipated benefit in erectile function and urinary continence has not been ascertained.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable interest in urethral-sparing cystectomy and preservation of the gynecological tract to maintain continence mechanism, sexual function, and reproductive function in young patients who undergo radical cystectomy for muscle-invasive bladder cancer and gained acceptance in many centers [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of oncological safety of a urethra and anterior vaginal wall-sparing cystectomy in selected patients has been addressed by several authors [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation